Japan's Foreign Assets and Liabilities : Implications for the External Accounts - Colacelli, Mariana (IMF Working Papers; Working Paper ;, 2021)
The composition of Japan's current account balance has changed over time, with an increasing income balance primarily reflecting a growing net foreign asset position and higher corporate saving. A comparison of Japan's income balance with peer countries highlights: (i) relatively high yields on FDI assets, and (ii) very low FDI liabilities in Japan. Panel estimation is used to derive separate exchange rate elasticities for income credit and debit, with novel accounting that disentangles the mechanical from the economic response to exchange rate fluctuations. Despite the changing composition of Japan's current account balance, its response to exchange rate movements still operates mostly through the traditional trade channel, with a small but reinforcing contribution from the income balance.